Evaluation of antibiotic prescribing pattern and appropriateness among hospitalized pediatric patients: findings from a Malaysian teaching hospital - Akkawi, Muhammad Eid; Taffour, Randa Mahmoud; AL-Shami, Abdulkareem Mohammed (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Background: Antibiotics are commonly prescribed for hospitalized children. However, only a limited number of studies have evaluated antibiotic use in this population. The current work assessed the indication, prescribing pattern and appropriateness of antibiotics among pediatric inpatients.